2017
DOI: 10.1155/2017/8243204
|View full text |Cite
|
Sign up to set email alerts
|

A Case with Severe Endometriosis, Ovarian Hyperstimulation Syndrome, and Isolated Unilateral Pleural Effusion after IVF

Abstract: We present a very rare case of right-sided isolated pleural effusion in a patient with severe endometriosis who, in relation to in vitro fertilization (IVF), developed ovarian hyperstimulation syndrome (OHSS). Earlier laparotomy showed grade IV endometriosis including endometriotic implants of the diaphragm. The patient had no known risk factors for OHSS and only a moderate number of oocytes aspirated. She received, however, repeated hCG injections for luteal support. The patient did not achieve pregnancy but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…There is a report of hemothorax in a patient submitted to IVF, which occurred in association with severe endometriosis with involvement of the diaphragm ( Sopa et al ., 2017 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a report of hemothorax in a patient submitted to IVF, which occurred in association with severe endometriosis with involvement of the diaphragm ( Sopa et al ., 2017 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of spontaneous hemothorax in patients with COVID-19 is a very rare presentation ( Halvorson et al ., 2012 ; Sopa et al ., 2017 ) , and the cases reported occurred during the acute phase of the disease ( Long & Grimaldo, 2021 ) . The association of spontaneous hemothorax with in vitro fertilization (IVF) procedures is rare and has been associated with thoracic endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Being familiar with the underlying risk factors could act as a predictor for OHSS and preventive measures could be taken before its occurrence. Studies have demonstrated that the incidence of moderate-to-severe OHSS occurs in approximately 1%-5% of all women undergoing treatment of infertility [4,5] . A wide spectrum of presentations related to OHSS have been reported in the past, ranging from mild isolated pleural effusions, effusions with accompanying abdominal ascites, to acute respiratory failure and shock [5,6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that the incidence of moderate-to-severe OHSS occurs in approximately 1%-5% of all women undergoing treatment of infertility [4,5] . A wide spectrum of presentations related to OHSS have been reported in the past, ranging from mild isolated pleural effusions, effusions with accompanying abdominal ascites, to acute respiratory failure and shock [5,6,7] . I hereby present a rare case of OHSS with an isolated large pleural effusion in the right hemithorax following ongoing cycles of IVF, ultimately resulting in respiratory compromise.…”
Section: Introductionmentioning
confidence: 99%
“…O zamandan bu yana sadece birkaç vaka raporu yayınlanmıştır ve bu olguların hiçbiri endometriozise sahip değildir (11)(12)(13)(14). Daha önce tarif edildiği gibi, plevral efüzyon esas olarak şiddetli OHSS formlarında ve genel olarak diğer OHSS bulgularıyla birlikte ortaya çıkmaktadır (15). Man ve ark.…”
unclassified